2009
DOI: 10.4155/fmc.09.22
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Nature as a Source of New Probes for Opioid Pharmacology

Abstract: The strong history of natural products as opioid receptor ligands suggests that nature is one of the most promising for the identification of novel opioids. This review highlights the vast potential of investigating natural products as novel probes of opioid receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 134 publications
0
6
0
Order By: Relevance
“…Despite the large amounts of articles reporting on the pharmacological activities of flavonoids, relatively few studies on the opioid receptors’ binding affinity of these compounds have been reported. In some works it has been demonstrated that the antinociceptive effect exerted by flavonoids in mouse thermal models of nociception was related to the activation of the opioid receptors. , Although some hydroxyflavones have been identified as opioid antagonists, none have been shown to inhibit morphine-induced antinociception in an animal model of acute pain. As far as we know, we reported for the first time that a flavone administered intraperitoneally in mice significantly reduced morphine-induced antinociception in a dose-dependent manner in the tail-flick test and that, in all probability, its action is mediated, at least in part, by opioid receptors.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the large amounts of articles reporting on the pharmacological activities of flavonoids, relatively few studies on the opioid receptors’ binding affinity of these compounds have been reported. In some works it has been demonstrated that the antinociceptive effect exerted by flavonoids in mouse thermal models of nociception was related to the activation of the opioid receptors. , Although some hydroxyflavones have been identified as opioid antagonists, none have been shown to inhibit morphine-induced antinociception in an animal model of acute pain. As far as we know, we reported for the first time that a flavone administered intraperitoneally in mice significantly reduced morphine-induced antinociception in a dose-dependent manner in the tail-flick test and that, in all probability, its action is mediated, at least in part, by opioid receptors.…”
Section: Resultsmentioning
confidence: 99%
“…Bioassays with a series of other natural flavonoids including catechin ( 5 ) and hesperetin ( 6 ) have been conducted and demonstrate that this scaffold may have considerable potential for development of opioid receptor ligands . Other structural subtypes with opioid-binding activity are becoming more common, including stilbenoids more reminiscent of the pawhuskins such as resveratrol ( 7 ) , and, more recently, chlorophorin ( 8 ) …”
mentioning
confidence: 99%
“…A minor pathway uses the same three-enzyme process. First, codeine-O-demethylase converts thebaine to the 3-phenol, oripavine (30), which is 6-O-demethylated and epimerized as described above (thebaine 6-O-demethylase) to afford morphinone (31). Ketone reduction (codeinone reductase) converts morphinone to morphine.…”
Section: ■ Street Namesmentioning
confidence: 99%
“…In a broader sense, the isolation of morphine from P. somniferum revolutionized the field of natural product-based drug discovery. , Plants and herbs, used for centuries by diverse cultures to treat disease, presented problems for Western medical practitioners. For one, Western medicinewhich relies on empiric, evidence-based treatmentssuffered from a lack of standardized biologic material with which to perform controlled clinical trials.…”
Section: Introductionmentioning
confidence: 99%